Two new species of geckos of the genus Phyllopezus Peters, 1878 (Squamata: Gekkota: Phyllodactylidae) from northeastern Brazil - Dubeux, Marcos J. M.; Gonçalves, Ubiratan; Palmeira, Cristiane N. S.; Nunes, Pedro M. S.; Cassimiro, José; Gamble, Tony; Werneck, Fernanda P.; Rodrigues, Miguel T.; Mott, Tamí (Zootaxa, 2022)
We describe two new species of Brazilian geckos of the genus Phyllopezus based on morphological and molecular data. The first species is currently known from a relictual Cerrado enclave—“campos rupestres”, in the mountains of the Serra do Espinhaço in the state of Bahia. The second species is known from northeastern Atlantic Forest and transitional areas with Caatinga biome in the state of Alagoas. The two new species are sister taxa and together are the sister clade to the remaining species in the Phyllopezus pollicaris species complex. These new species can be morphologically distinguished from their congeners by meristic and morphometric characters, in addition to color pattern and genetic differentiation.